The Firstborn of Death: Monotheism and the Mythology of Death in Job 18 - Brown, Ken (Vetus Testamentum, 2019)
Job 18 depicts the destruction of the wicked as a kind of ambush by "the firstborn of death." Much of the discussion of this passage has centered on this figure's identification, and whether one should look primarily to Ugaritic or Mesopotamian mythological traditions for its background. Yet the passage as a whole concludes with a reference to a single "God," knowledge of whom is determinative for human fate. This raises a basic question concerning the relation between "God" and the "firstborn of death." Through a close comparison with the Ugaritic Baal Cycle and the Neo-Assyrian Underworld Vision on the one hand, and Job 5 and Deuteronomy 32 on the other, this paper argues that "the firstborn of death" most likely does represent a chthonic deity, but that such powers have been subordinated to the one God whom Bildad presumes to bear sole authority over life and death.